Educational videos used by professors and english students of the send-and third year level for the teaching and learning of the english language at Centro Regional Universitario de Veraguas Year 2022 - Bultrón, Viviana
General objective: The study vas onented toward the foliowing objectives: To determine the educational videos used by second and third-year English students in learning the English language at the Centro Regional Universitario de Veraguas.To know the educational videos used by professors in teaching the English language at the Centro Regional Universitario de Veraguas. Specific objectives: To recognize the educational videos used by the professor in the teaching process with second-and third-year students of English. To describe the actual use the student makes with the educational videos in learning the English language in the classroom and outside of it. To indicate the limitations presented by the professor and student for the efficient use of educational videos in the classroom and outside of it.